Chapter Phytoplankton assemblage Characterization along the Mediterranean coast of Morocco during autumn - Idmoussi, Hajar (Proceedings e report, 2020)
The present study aimed to assess the composition, abundance and diversity of phytoplankton assemblage along the Moroccan Mediterranean Coast. Phytoplankton samples were collected in October 2018 at 48 stations from M'diq bay in the West to Saïdia in the East. 92 taxa have been inventoried, belonging to five groups. Diatoms dominate qualitatively and quantitatively (85.5%), followed by dinoflagellates (12%). Phytoplanktonic diversity and abundance was pronounced in the western part of Moroccan Mediterranean Sea, especially (from Jebha to M'diq) because of the influence of the Atlantic flow.